(untitled) (Research, Society and Development, 2021)
The concern with soil compaction has increased due to the high traffic of machinery and equipment in a no-tillage system. With this, there is low water infiltration, which affects the dynamics of nutrients in the soil. Thus, the objective of this work was to evaluate the uptake of soybean nutrients under soil compaction levels (1.1; 1.2; 1.3; 1.4 and 1.5 Mg ha-1). The work was carried out in a protected environment at the State University of West Paraná, Cascavel Campus, in a completely randomized design, with five replications. The experiment was set up with overlapping PVC rings, 5 cm, 10 cm and 20 cm in height. The 20 cm PVC ring contained uncompacted soil. Over these, the 5 cm PVC ring with the compaction levels was placed and, lastly, above all, the third 10 cm PVC ring with uncompacted soil. Nutrient uptake by soybean plants was analyzed in the R1 development phase. Soil compaction induced alterations in the uptake and concentration of P, K and Mg in soybean plants. An increase in P and K contents was observed with increasing compaction, which was due to the greater contact between soil and root due to the confinement of the roots in the upper layer of compacted soil.